2021
DOI: 10.1097/ta.0000000000003138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injury location and severity on opioid use after trauma

Abstract: Recent data have suggested that persistent opioid use is prevalent following trauma. The effect of type of injury and total injury burden is not known. We sought to characterize the relationship between injury location and severity and risk of persistent opioid use. METHODS:We investigated postdischarge opioid utilization among patients who were admitted for trauma between January 2010 and June 2017 using the Optum Clinformatics Database. New persistent opioid use (NPOU) was defined as one of the following sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Only 8% of the trauma patients became long-term opioid users. Even though a lower number would be desirable, this percentage is comparable to the prevalence of prolonged opioid use in other studies [29][30][31]. Furthermore, some other studies reported an even higher prevalence of opioid use after musculoskeletal trauma at discharge from the hospital as well as in the longer term (54.3-97.1% and 19.7-35.3%, respectively) [32][33][34][35].…”
Section: Discussionsupporting
confidence: 55%
“…Only 8% of the trauma patients became long-term opioid users. Even though a lower number would be desirable, this percentage is comparable to the prevalence of prolonged opioid use in other studies [29][30][31]. Furthermore, some other studies reported an even higher prevalence of opioid use after musculoskeletal trauma at discharge from the hospital as well as in the longer term (54.3-97.1% and 19.7-35.3%, respectively) [32][33][34][35].…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies of persistent opioid use have used a variable duration of follow-up, ranging from 30 to 365 days after a defined event, with most selecting a 3-to 6-month interval. [10][11][12][25][26][27][28] The variability in defining persistent opioid use was highlighted in a 2020 analysis of the existing literature, where the authors found 29 distinct definitions across 39 different studies. 29 We selected and would advocate that a long length of follow-up should be used for trauma patients given the heterogeneity of this population.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of interest in this study was persistent long-term opioid use after trauma, which we defined as evidence of continued opioid use at 1 year following discharge. Previous studies of persistent opioid use have used a variable duration of follow-up, ranging from 30 to 365 days after a defined event, with most selecting a 3- to 6-month interval 10–12,25–28 . The variability in defining persistent opioid use was highlighted in a 2020 analysis of the existing literature, where the authors found 29 distinct definitions across 39 different studies 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations